Survey of Cultivated Vegetable Crops in Rupandehi District, Nepal - Thapa, Chandra Bahadur (Himalayan Biodiversity, 2017)
Vegetable is very nutritious food and is considered to be protective food since it contains high amount of vitamins and minerals and also possesses medicinal value. In the present study, documentation of farmer’s knowledge on cultivated vegetable crops was carried out in Rupandehi district during the year 2016. The objective of this paper is to identify, enumerate and to know the status of vegetable crops in this district. It was carried out by conducting semi-structured interview with the vegetable growing farmers, local people, members of Community Based Organizations with the help of standard questionnaire, checklist, Focus Group Discussion (FGD) and key informant interview. Altogether 50 plant species have been found to be cultivated in commercial scale as vegetable crops in Rupandehi district. Out of 50 plant spp.; 2 families, 4 genera and 5 spp. were monocots; and 9 families, 30 genera and 45 spp. were dicots. It is also found that fruit (55%) is the widely used part of plant as vegetable. Other parts like leaf (21%), inflorescence (4%), root (8%), tuber (2%), corm (6%), and bulb (4%) are also used as vegetable. Most of the vegetable growing farmers (91%) are economically benefited by the cultivation and selling of vegetable than other crops due to easily available seeds, fertilizers and pesticides in market; good facility of irrigation and accessible market in the study area.